Platelet surface expression of SDF-1 is associated with clinical outcomes in the patients with cardiovascular disease. (2nd January 2017) - Rath, Dominik; Chatterjee, Madhumita; Bongartz, Angela; Müller, Karin; Droppa, Michal; Stimpfle, Fabian; Borst, Oliver; Zuern, Christine; Vogel, Sebastian; Gawaz, Meinrad; Geisler, Tobias
Abstract: Platelet surface expression levels of stromal cell derived factor 1 (SDF-1) are elevated in acute coronary syndrome and associated with LVEF% improvement after myocardial infarction (MI). Platelet SDF-1 might facilitate thrombus formation and endomyocardial expression of SDF-1 is enhanced in inflammatory cardiomyopathy and positively correlates with myocardial fibrosis. The influence of platelet SDF-1 on outcome in the patients with symptomatic coronary artery disease (CAD) is to the best of our knowledge unknown. Blood samples of 608 consecutive CAD patients were collected during the percutaneous coronary intervention and analyzed for surface expression of SDF-1 by flow cytometry. The primary combined endpoint was defined as the composite of either MI, or ischemic stroke, or all-cause death. Secondary endpoints were defined as the aforementioned single events. The patients with baseline platelet SDF-1 levels above the third quartile showed a significantly worse cumulative event-free survival when compared to the patients with lower baseline SDF-1 levels (first to third quartile) (log rank 0.009 for primary combined endpoint and log rank 0.016 for secondary endpoint all-cause death). Multivariate Cox regression analysis showed that SDF-1 levels above the third quartile were independently associated with the primary combined endpoint and the secondary endpoint all-cause death. We provide first clinical evidence that high platelet expression levels of SDF-1 influence clinical outcomes in CAD patients in a negative way.